SUHRAWARDĪ’S CONCEPT OF ILLUMINATION AND ITS RELEVANCE TO ENVIRONMENTAL CONSERVATION AWARENESS: A SUFI ECOLOGICAL APPROACH - Ihsan, Nur Hadi; Mudin, Moh. Isom; Dewantara, Mawardi (Sekolah Tinggi Agama Islam Sadra, 2024)
This study investigates Shihāb al-Dīn al-Suhrawardī's sufi philosophy of illumination and explores its potential contribution to contemporary environmental consciousness. The increasingly urgent global ecological crisis has sparked interdisciplinary debate about root causes and comprehensive solutions. Several contemporary thinkers argue that the ecological crisis is a manifestation of a more fundamental ontological crisis, namely the loss of humans' harmonious relationship with nature. In this context, Islamic philosophy, especially the school of illumination (ishrāq) developed by Shihāb al-Dīn al-Suhrawardī, offers a unique perspective that can enrich environmental discourse. The research aims to integrate Suhrawardī’s ontological and epistemological concepts with contemporary ecological principles to offer a novel perspective on human-nature relationships. A descriptive-analytical approach is employed to analyze Suhrawardī’s philosophical texts and correlate them with modern ecological theories. The study reveals that Suhrawardī’s concept of asala al-mahiya (essential reality) and his illuminationist epistemology, which views all beings as emanations of divine light, challenge the anthropocentric worldview. This perspective promotes two fundamental ecological principles: biospherical illuminative egalitarianism and illuminative equilibrium. These principles emphasize social justice and environmental balance, recognizing humans as integral parts of nature with responsibility for its preservation. By shifting the human-nature relationship from a subject-object dichotomy to an inter-subject interaction, Suhrawardī’s philosophy can enhance awareness of environmental issues and inspire more sustainable practices. Integrating spiritual wisdom and ecological consciousness offers a holistic approach to addressing contemporary environmental challenges.